Biochemical Alterations in Cellulose, Hemicellulose, and Lignin during Fungal Colonization of Brassica Leaf Litter - Balamurugan, Merlin (Journal of Research in Science and Engineering, 2025)
Decomposition of plant litter is a fundamental ecological process, with microfungi playing a key role in breaking down complex organic compounds. This study investigates the biochemical changes in cellulose, hemicellulose, and lignin during fungal colonization of Brassica campestris L. leaf litter. A controlled litterbag experiment was conducted over 180 days to analyze fungal succession and biochemical composition. The results indicated a progressive reduction in cellulose (95%), hemicellulose (92%), and lignin (40%) as fungal decomposition progressed. Early-stage colonizers, including Aspergillus and Penicillium, utilized soluble carbohydrates, whereas cellulolytic fungi like Trichoderma and Chaetomium dominated the intermediate phase. In the final stages, ligninolytic fungi such as Curvularia and Alternaria contributed to lignin breakdown. The findings highlight the efficiency of fungal- mediated decomposition in nutrient cycling and suggest potential applications in sustainable agriculture and organic waste management.